Splatoon. Vol. 4 - Hinodeya, Sankichi; Hurley, Jason A., 1981- (Viz Media, 2018)
"The preliminary rounds have come to a close! And Team Blue has made up. As the Inklings gear up for the main round of the Square King Cup, they must prepare for all kinds of teams that are way stronger than they are, and may even have to battle the undisputed Splatoon champion--the player known as Emperor!"--Page [4] of cover.